TRIAL OF PROGRAMMING EDUCATION FOR DEVELOPING ABILITIES OF SHIFTING VIEWPOINT IN ELEMENTARY SCHOOLS: THROUGH PROGRAMMING LEARNING ACTIVITIES USING ROBOTS: Received: 20th January 2025, Revised: 21th February 2025, 12th March 2025, Accepted: 3rd April 2025, Date of Publication: 15th July 2025 - Hironori Sasaki (PUPIL: International Journal of Teaching, Education and Learning, 2025)
We organised learning activities for programming with a humanoid robot “Robohon” and conducted trial lessons with 73 third-grade elementary school students with the aim of cultivating their ability to shift their viewpoint at the physical level, the social level, and the third-person viewpoint. By shifting the viewpoint to Robohon the programming activities were adopted as those for cultivating each skill in the class. To measure the effectiveness of the learning activities, four tasks were used. The first was based on Piaget’s "Three Mountains Problem", the second was a task to examine the developmental level of the role-taking ability, and the third task was a "Sally and Anne" test to measure the taking of a third-person viewpoint. Those were used in the pre- and post- surveys. Also included in the evaluation was a task to create a flowchart that the children produced in class. As a result of the study, no significant effects on these three abilities were confirmed from the pre- and post-surveys using the three tasks, but the flowchart worksheets created in class indicated that the children were thinking from the viewpoint of others.